Isolation and Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) from Milk in Shire Dairy Farms, Tigray, Ethiopia - Weldemelak Girmay; Getachew Gugsa; Habtamu Taddele; Yisehak Tsegaye; Nesibu Awol; Meselu Ahmed; Aklilu Feleke (Veterinary Medicine International)
Antibiotic-resistant Staphylococcus aureus isolates pose a severe challenge to both veterinary and health professions and dairy cattle producers. Cross-sectional study was conducted from November 2014 to May 2015 to isolate and identify S. aureus from mastitic cows’ milk and estimate the occurrence of MRSA in the dairy farms of Shire. Physical examination and California mastitis test were performed on a total of 220 dairy cows. Bacteriological isolation and identification and antibiogram testing were performed. Furthermore, multiplex polymerase chain reaction (PCR) was done for the detection of mec A and fem A genes. Out of the 220 dairy cows, 64 (29.09%) were positive for bovine mastitis, and of these, 32.81% were coagulase-positive S. aureus (CoPS). Antibiogram test results showed 100% of the isolates were resistant to penicillin G, nalidixic acid, and ampicillin, and 33.33% of the CoPS showed resistance to oxacillin (phenotypically MRSA positive). But 38.09% of the CoPS were found to be resistant and susceptible to vancomycin. PCR amplification of the seven phenotypically MRSA isolates revealed that 42.9% and 71.4% of them were found to carry fem A and mec A genes, respectively. The current study revealed the existence of alarming level of CoPS and development of multidrug resistance.